Innovations and Challenges by Applying Sublingual Laser Blood Irradiation in Juvenile Idiopathic Arthritis - Laura Marinela Ailioaie; Gerhard Litscher; Michael Weber; Constantin Ailioaie; Daniela Litscher; Dragos Andrei Chiran (International Journal of Photoenergy)
Sublingual laser blood irradiation (SLBI) was applied into a randomized, single-blind, placebo-controlled study in juvenile idiopathic arthritis (JIA), aimed at inducing disease remission. 105 children with JIA, without an adequate response to classical treatment, were administrated a disease modifying drug (Methotrexate) and were randomly assigned to three groups. Group I (36 patients) received SLBI with the Weberneedle Lasershower Mouth Applicator with three wavelengths (635 nm, 536 nm, and 405 nm), 5 mW maximum output power each, in continuous mode, simultaneously, for 20 minutes daily, 7 successive sessions per month, repeated every 7 weeks, for three times. Group II (36 patients) received placebo SLBI. Group III (33 patients) received only treatment with Methotrexate. Evaluation was performed using American College of Rheumatology Pediatric criteria (ACR Pedi) at study enrollment and at 8, 16, 24, and 48 weeks. At the end of study, there was an improvement of the ACR Pedi 30 by 86.11% in SLBI group compared to only 61.11% in Group II, respectively, and 60.6% in Group III (P=0.001), with significant statistical differences. SLBI has reduced the pain, lowered the number of articulations with movement limitation, increased the quality of life, and made it possible to avoid the administration of biological agents.